By Binding CD80 and CD86, the Vaccinia Virus M2 Protein Blocks Their Interactions with both CD28 and CTLA4 and Potentiates CD80 Binding to PD-L1 - Kleinpeter, Patricia (J Virol, 2019)
In this article we report that the M2 protein encoded by the vaccinia virus is secreted as a homo-oligomer by infected cells and binds two central costimulation molecules, CD80 (B7-1) and CD86 (B7-2). These interactions block the ligation of the two B7 proteins to both soluble CD28 and soluble cytotoxic T-lymphocyte associated protein 4 (CTLA4) but favor the binding of soluble PD-L1 to soluble CD80. M2L gene orthologues are found in several other poxviruses, and the B7-CD28/CTLA4 blocking activity has been identified for several culture supernatants of orthopoxvirus-infected cells and for a recombinant myxoma virus M2 protein homolog (i.e., Gp120-like protein, or Gp120LP). Overall, these data indicate that the M2 poxvirus family of proteins may be involved in immunosuppressive activities broader than the NF-κB inhibition already reported (R. Gedey, X. L. Jin, O. Hinthong, and J. L. Shisler, J Virol 80:8676–8685, 2006, https://doi.org/10.1128/JVI.00935-06). A Copenhagen vaccinia virus with a deletion of the nonessential M2L locus was generated and compared with its parental virus. This M2L-deleted vaccinia virus, unlike the parental virus, does not generate interference with the B7-CD28/CTLA4/PD-L1 interactions. Moreover, this deletion did not affect any key features of the virus (in vitro replication, oncolytic activities in vitro and in vivo, and intratumoral expression of a transgene in an immunocompetent murine model). Altogether, these first results suggest that the M2 protein has the potential to be used as a new immunosuppressive biotherapeutic and that the M2L-deleted vaccinia virus represents an attractive new oncolytic platform with an improved immunological profile. IMPORTANCE The vaccinia virus harbors in its genome several genes dedicated to the inhibition of the host immune response. Among them, M2L was reported to inhibit the intracellular NF-κB pathway. We report here several new putative immunosuppressive activities of M2 protein. M2 protein is secreted and binds cornerstone costimulatory molecules (CD80/CD86). M2 binding to CD80/CD86 blocks their interaction with soluble CD28/CTLA4 but also favors the soluble PD-L1-CD80 association. These findings open the way for new investigations deciphering the immune system effects of soluble M2 protein. Moreover, a vaccinia virus with a deletion of its M2L has been generated and characterized as a new oncolytic platform. The replication and oncolytic activities of the M2L-deleted vaccinia virus are indistinguishable from those of the parental virus. More investigations are needed to characterize in detail the immune response triggered against both the tumor and the virus by this M2-defective vaccinia virus.